\(\dfrac{3}{8}:1=\dfrac{3}{8}\)
vì số nào chia cho 1 cũng bằng chính số đó
\(\dfrac{3}{8}\) : 1=\(\dfrac{3}{8}\) : \(\dfrac{1}{1}\)= \(\dfrac{3x1}{8x1}=\dfrac{3}{8}\)
\(\dfrac{3}{8}:1=\dfrac{3}{8}\)
Vì số nào chia cho 1 cx = chính nó
\(\dfrac{3}{8}:1=\dfrac{3}{8}\)
vì số nào chia cho 1 cũng bằng chính số đó
\(\dfrac{3}{8}\) : 1=\(\dfrac{3}{8}\) : \(\dfrac{1}{1}\)= \(\dfrac{3x1}{8x1}=\dfrac{3}{8}\)
\(\dfrac{3}{8}:1=\dfrac{3}{8}\)
Vì số nào chia cho 1 cx = chính nó
\(\dfrac{2}{5}\) x \(\dfrac{3}{4}-\dfrac{1}{8}\) \(= \)
\(\dfrac{4}{3}+\dfrac{1}{3}-\dfrac{1}{5}=\)
\(\dfrac{9}{20}-\dfrac{3}{5}\) x \(\dfrac{1}{4}\)\(= \)
\(\dfrac{2}{8}+\dfrac{2}{3}:\dfrac{4}{5}\)\(=\)
\(\dfrac{3}{5}+\dfrac{1}{2}+\dfrac{8}{15}\)
\(\dfrac{6}{9}+\dfrac{14}{18}-\dfrac{5}{6}\)
\(\dfrac{9}{20}-\dfrac{3}{5}:\dfrac{4}{1}\)
\(\dfrac{1}{6}+\dfrac{2}{3}\) x \(\dfrac{8}{9}\)
\(3-\dfrac{8}{13}-\dfrac{2}{13}-\dfrac{3}{13}\)
\(\dfrac{8}{10}+\dfrac{1}{5}-\dfrac{1}{4}-\dfrac{15}{20}\)
A,\(\dfrac{8}{9}:\dfrac{4}{5}+\dfrac{3}{5}\)
B,\(\dfrac{5}{8}\) + \(\dfrac{1}{4}\)
C,\(\dfrac{7}{8}\) x \(\dfrac{4}{7}\) +\(\dfrac{5}{9}\)
D,\(\dfrac{9}{8}:\dfrac{4}{3}-\dfrac{4}{7}\)
Tính nhanh:
\(\dfrac{9}{8}x\dfrac{8}{7}x\dfrac{7}{3}x\dfrac{1}{3}\)
a)\(\dfrac{3}{5}\)+\(\dfrac{17}{21}\)*\(\dfrac{17}{21}\)+\(\dfrac{3}{5}\)
b)\(\dfrac{15}{8}\):\(\dfrac{5}{20}\)-\(\dfrac{7}{8}\):\(\dfrac{1}{4}\)
tính
\(\dfrac{27}{15}\)+\(\dfrac{6}{8}\)
\(\dfrac{19}{24}\)+\(\dfrac{7}{18}\)
\(\dfrac{2}{9}\)-\(\dfrac{1}{6}\)
\(\dfrac{8}{15}\)-\(\dfrac{1}{3}\)
Tính :
a) 7 x \(\dfrac{3}{14}\) - \(\dfrac{1}{14}\) b) \(\dfrac{3}{2}\) + \(\dfrac{7}{4}\) x \(\dfrac{2}{5}\)
c) \(\dfrac{9}{8}\) : 3 + \(\dfrac{7}{8}\) : 3 d) 2 : \(\dfrac{3}{4}\) - \(\dfrac{5}{8}\) x \(\dfrac{4}{3}\)
\(x +\dfrac{5}{9} =\dfrac{4}{3}\)
\(x -\dfrac{4}{9}=\dfrac{2}{3}\)
\(\dfrac{5}{8}+x=\dfrac{8}{5} \)
\(\dfrac{5}{6}-x=\dfrac{1}{12}\)
a,5+\(\dfrac{2}{3}\)
b,\(\dfrac{15}{5}\)x\(\dfrac{1}{4}\)
c.\(\dfrac{3}{8}\)\(-\)\(\dfrac{1}{3}\)
d,\(\dfrac{6}{15}\)\(-\)\(\dfrac{1}{3}\):\(\dfrac{5}{3}\)